2001
DOI: 10.1089/107999001750169871
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-6 Production by Endothelial Cells via Stimulation of Protease-Activated Receptors Is Amplified by Endotoxin and Tumor Necrosis Factor-α

Abstract: Human endothelial cells respond to extracellular proteases, endotoxin (lipopolysaccharide, LPS), and inflammatory cytokines. Endothelial cells express several protease-activated receptors (PAR), including the thrombin-activated receptors PAR-1 and PAR-3 and a thrombin-independent, protease-activated receptor, PAR-2. To examine the potential cooperation between PAR and inflammatory stimuli, we investigated the effects of the PAR-1 agonist peptide Ser-Phe-Leu-Leu-Arg-Asn (SFLLRN) and PAR-2 agonist peptide Ser-Le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
96
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 126 publications
(100 citation statements)
references
References 41 publications
4
96
0
Order By: Relevance
“…39 Others have reported that activation of PAR induced detectable levels of IL-6 production in a dose-dependent fashion. 40 Our results indicated that PAR4 mRNA was up-regulated in response to all three stimuli. As mast cells and tryptase are common features of IC, it is tempting to suggest that tryptase generated during the mast cell degranulation along with an up-regulation of PAR4 may contribute to abnormal neurotransmission and motility in the inflamed bladder.…”
Section: Par and Tryptasementioning
confidence: 52%
“…39 Others have reported that activation of PAR induced detectable levels of IL-6 production in a dose-dependent fashion. 40 Our results indicated that PAR4 mRNA was up-regulated in response to all three stimuli. As mast cells and tryptase are common features of IC, it is tempting to suggest that tryptase generated during the mast cell degranulation along with an up-regulation of PAR4 may contribute to abnormal neurotransmission and motility in the inflamed bladder.…”
Section: Par and Tryptasementioning
confidence: 52%
“…Increasing interest is now focused on the role of COX-2 and prostanoid homeostasis in the pathogenesis of atherosclerosis (21). Previous reports from our laboratory have documented the ability of mast cell proteases and histamine to interact with endothelial cells and enhance inflammatory responses, as determined by the production of IL-6 and IL-8 (9,22,23) and expression of TLR2 and TLR4 (16). In the present study, we demonstrate that histamine, acting through H 1 R, selectively induces the expression of functionally active COX-2 and stimulates the production of PGI 2 and PGE 2 in HCAEC.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, several studies have investigated the possible connection between PAR 2 -and TLR4-mediated signaling pathways. For example, concurrent activation of PAR 2 and TLR4 by PAR 2 AP and LPS, respectively, amplifies NF-B activation and IL-6 production in endothelial cells (37). In contrast, the inflammatory response induced by Aspergillus infection involves TLR4-mediated suppression of PAR 2 signaling (36).…”
Section: Ap-inducible Nf-b Reporter Activation That Was Protein Synthmentioning
confidence: 99%